ANALISIS DAMPAK KUALITAS PELAYANAN AKADEMIK TERHADAP LOYALITAS MAHASISWA DENGAN KEPUASAN MAHASISWA SEBAGAI VARIABEL INTERVENING - Ali Hanafiah (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
The aim of this study was 1) to determine and analyze the effect of quality of academic services to the satisfaction of students in the graduate program Mercu Buana University, 2) To know and analyze the influence of Quality of Academic Services for loyalty Students in graduate programs Mercu Buana University, 3) To know and analyze the influence of the Student Satisfaction Loyalty program graduate student at the University of Mercu Buana, and 4) To determine and analyze the effect of quality of academic services to students through Student Satisfaction Loyalty program Mercu Buana University graduate. Data analysis method used in analyzing the influence or relationship between the dependent variable and independent variables through an intervening variable. The method used is the analysis Path (Path Analysis). The results showed a significant difference between the quality of academic services for student satisfaction, it can be interpreted that if the quality of academic services performed Mercu Buana University graduate programs to students further improved, it will increase student satisfaction. The quality of academic services affect the loyalty of students, giving the sense that the higher the quality of academic services provided to the students, the more it will increase the loyalty of the students in the use of educational services in the graduate program Mercu Buana University. There is a significant relationship between student satisfaction to loyalty of students, it can be interpreted that if the level of student satisfaction increases, the loyalty of the student will also increase. Student satisfaction is able to become an intervening variable between academic service quality and loyalty of students, it can be interpreted that the higher the quality of academic services provided, it will increase the level of satisfaction of the students, so it will have an impact on increasing the loyalty of the students.Keywords: Academic Services satisfaction, student satisfaction and loyalty.